2016
DOI: 10.1590/0034-737x201663010005
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic correlations and path analysis for plant architecture traits and grain production in three generations of cowpea

Abstract: RESUMOThe objective of this study was to analyze the phenotypic correlation and path analysis of traits related to plant architecture, earliness and grain yield in F 2 , RC 1 and RC 2 generations, from crosses between cowpea cultivars BRS Carijó and BR14 Mulato. Most phenotypic correlations of the examined traits were concordant in statistical significance, with approximate values among the examined generations. For the trait seed weight, significant and positive phenotypic correlations were observed in the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…These results allow us to infer that leaf fall in the reproductive phase depends mainly on the supply of organic fertilizer in the soil, which indicates a reduction in the crop cycle. According to Ribeiro et al (2016) there is a high association between architecture and precocity of grain production. Carvalho et al (2003), state that there is an association between chlorophyll concentration, N content in leaves and grain yield in beans.…”
Section: Discussionmentioning
confidence: 99%
“…These results allow us to infer that leaf fall in the reproductive phase depends mainly on the supply of organic fertilizer in the soil, which indicates a reduction in the crop cycle. According to Ribeiro et al (2016) there is a high association between architecture and precocity of grain production. Carvalho et al (2003), state that there is an association between chlorophyll concentration, N content in leaves and grain yield in beans.…”
Section: Discussionmentioning
confidence: 99%
“…According to Coelho et al (2002), the number of pods per plant showed a high correlation with grain yield in the summer-autumn season. According to Ribeiro et al (2016), the direct effects of phenotypic correlations indicate the true association between architecture and precocity of grain production.…”
Section: Path Analysis Between Agro-morphological Charactersmentioning
confidence: 99%
“…Therefore, effective selection requires information on correlations between grain yield and other traits, including components. However, this correlation does not clearly discriminate the direct and indirect effects of such traits because of alterations that may occur because of the selection pressure (Bhatt, 1973;Ribeiro et al, 2016).…”
mentioning
confidence: 98%
“…For cowpea beans, the identification of direct and indirect effects of independent traits is important in the selection of cultivars that can satisfy Colombia's needs. This technique has been applied in the genus Vigna by Meena et al (2015); Hemavathy et al (2015); and Ribeiro et al (2016).…”
mentioning
confidence: 99%